Decision Support System for Laptop Selection Recommendations Using the Weigted Product (WP) Method - Muris, Anggeraeni Agustin; Dapiokta, Jum; Wijaya, Johan Eka; Yunarti, Yelmi; Kuswanto, Joko (Universitas Pendidikan Nasional, 2024)
The many types of specifications, colors and brands of laptops are complicated and confusing for ordinary people who are going to buy laptops. The reason is, there are many variants of laptops on the market with different specifications. To help potential consumers in choosing a laptop that suits their needs, a decision support system (SPK) is needed that can provide the most appropriate laptop recommendations. This study discusses the decision support system for laptop selection recommendations using the Weighted Product (WP) method. This method is used to help consumers choose a laptop that suits their needs based on predetermined criteria, such as processor, RAM, Storage, and Price. After a search of the vector to get the ranking, the largest vector value of 0.124 was obtained on Sony, Appel, and Dell Alternatives to be recommended in the selection of laptops. Based on the results of the research, it can be concluded that the decision support system (SPK) with the Weighted Product (WP) method can provide laptop recommendations that suit the needs of users. This research provides benefits for users in choosing the right laptop that suits their needs. In addition, this research can also be the basis for the development of a decision support system for the selection of laptops or computers in other fields.